(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
In this paper authors analyse a case of Facebook which was assessed by German competition authority – Bundeskartellamt. Facebook has been suspected of abusing its dominant position in the context of protection of personal data. This case was subsequently considered by the competent national judicial authorities, which finally referred the questions to the Court of Justice of the European Union (Oberlandesgericht Düsseldorf ) in case C-252/21. At the present stage of the proceedings are published exclusively Application and Request for preliminary ruling. The authors aim heads to examine the disputed action of platform in the context of the proposed Digital Markets Act and to confront them with the obligations imposed by this proposal for a regulation for new category of entities – so called- gatekeepers.